Short Course Digital Marketing sebagai Sarana Meningkatkan Animo Pendaftar Peserta Didik Baru di SD Muhammadiyah Kalangan - Tri Kuat; Arief Kurniawan (Jurnal Surya Masyarakat, 2023)
The location of SD Muhammadiyah Kalangan is located in Baturetno Banguntapan Village, Bantul, located within the village and not located on the edge of the highway, so that the location is less strategic to get the attention of the community. Promotion of new student admissions at SD Muhammadiyah Kalangan every year is carried out conventionally and has not used digital marketing media. This condition makes it difficult for SD Muhammadiyah Kalangan to compete with elementary schools located near the location. Based on these conditions, a special strategy is needed so that SD Muhammadiyah Kalangan can be better known by the public in general. This community service aims to provide insight and training to schools on digital marketing as a means to increase the interest of new student registrants. The method used in this community service is by conducting Short Course Digital Marketing activities as well as assisting in the creation of digital marketing media by utilizing websites and social media. The Short Course will start on August 6-10, 2021, and will be attended by 10 participants, namely teachers and employees of SD Muhammadiyah Kalangan. Community service shows a good impact seen from the pre-test and post-test scores of the implementation of the Digital Marketing Short Course, namely there is an increase in understanding and skills about Digital Marketing to be used as a strategy to increase the interest of new student registrants and be able to compete with other schools in the environment in the digital age.